1986
DOI: 10.1161/01.cir.73.5.865
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstriction of stenotic coronary arteries during dynamic exercise in patients with classic angina pectoris: reversibility by nitroglycerin.

Abstract: To study the vasomotility of normal and diseased coronary arteries during dynamic exercise, symptom-limited supine bicycle exercise during cardiac catheterization was performed by 18 patients with classic angina pectoris. The cardiovascular response was assessed by hemodynamic measurements and computer-assisted determination of normal and stenotic coronary artery luminal areas from biplane coronary angiograms made before, during, and after exercise. After baseline measurements were recorded, 12 patients (group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(65 citation statements)
references
References 41 publications
4
58
0
1
Order By: Relevance
“…15 ' 62 ' 63 This abnormal vasoconstriction of coronary arteries may facilitate myocardial ischemia. 6465 In the present study, the decrease in coronary diameter observed during sympathetic stimulation (-8.2%) is quite substantial.…”
Section: Discussionmentioning
confidence: 99%
“…15 ' 62 ' 63 This abnormal vasoconstriction of coronary arteries may facilitate myocardial ischemia. 6465 In the present study, the decrease in coronary diameter observed during sympathetic stimulation (-8.2%) is quite substantial.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report' 4 ', we have shown that normal coronary arteries dilate during dynamic exercise, but eccentric coronary stenoses show exercise-induced coronary vasoconstriction. The exact mechanism of this exercise-induced stenosis narrowing is not clear but might be due to endothelial dysfunction (atherosclerotic alterations) with an insufficient production of the endothelium-derived relaxing factor' 45 ' or due to a passive collapse of the free vessel wall within the stenosis during high flow states (Venturi mechanism) such as bicycle exercise' 71 .…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, almost no comparative data exist in the literature and sample sizes are small, as is the case with our study population. Gage et al 21 and Gordon et al 25 have shown vasoconstriction of stenotic but vasodilation of normal coronary vessel segments in response to exercise. Recently, we reported that stent implantation does not impair exercise-induced coronary artery vasodilation proximal and distal to the stented vessel, 17 as it was reported by Caramori et al 26 Sabate et al 19 have reported preserved endothelium-dependent vasodilation 6 months after brachytherapy, assessed by the vasomotor response to acetylcholine infusion.…”
Section: Limitationsmentioning
confidence: 99%
“…Normal coronary arteries dilate during dynamic exercise. 21 Percutaneous transluminal coronary angioplasty of stenotic lesions normalizes or improves coronary vasomotion. 22 Stent implantation abolishes paradoxical vasoconstriction of coronary stenosis and renders a previous vasoresponsive vessel into a rigid tube.…”
Section: Pathophysiological Considerationsmentioning
confidence: 99%